Doxorubicin inhibits muscle inflammation after eccentric exercise. Issue 2 (10th October 2016) - Huang, Sheng‐Chih; Wu, Jin‐Fu; Saovieng, Suchada; Chien, Wei‐Horng; Hsu, Ming‐Fen; Li, Xiao‐Fei; Lee, Shin‐Da; Huang, Chih‐Yang; Huang, Chih‐Yang; Kuo, Chia‐Hua
Abstract: Background: Doxorubicin, a widely used anti‐tumour drug, is known to cause muscle loss in cancer patients. Methods: Following an acute dose of doxorubicin injection (2.5 mg/kg per body weight), we examined macrophage distribution in rat soleus muscle challenged by eccentric exercise (downhill running). Long‐term doxorubicin treatment (one injection every 3 days) on muscle mass and survival were also determined. Results: Under non‐exercised condition, increased tumour necrosis factor (TNF)‐alpha mRNA and decreased IL‐10 mRNA were observed in soleus muscle of doxorubicin‐treated rats, compared with saline‐treated control rats. However, increases in inflammation score (leukocyte infiltration), nitrotyrosine level, and M1 macrophage (CD68 + ) invasion in exercised soleus muscle were absent in doxorubicin‐treated rats, whereas increased M2 macrophage (CD163 + ) localization in exercised muscle was less affected by doxorubicin. Despites coenzyme Q (Q10) supplementation significantly elevated TNF‐alpha mRNA, nitrotyrosine, and anti‐oxidant gamma‐glutamylcysteine synthetase (GCS) levels in non‐exercised soleus muscle, these pro‐inflammatory responses were also abolished in doxorubicin‐treated rats. Results from long‐term doxorubicin treatment show a significant muscle loss followed by an accelerated death, which cannot be reversed by Q10 supplementation. Conclusions: (i) Doxorubicin impairs inflammation mechanism by depleting M1 macrophage in exercised skeletal muscle; (ii) Muscle loss and accelerated death during prolonged doxorubicin treatment cannot be reversed by Q10 supplementation.